2013
DOI: 10.1371/journal.pone.0069561
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and Its Allocation in Relation to Temperature, Precipitation, and Soil Nutrients in Inner Mongolia Grasslands, China

Abstract: AimUnderstanding and predicting ecosystem functioning such as biomass accumulation requires an accurate assessment of large-scale patterns of biomass distribution and partitioning in relation to climatic and soil environments.MethodsWe sampled above- and belowground biomass from 26 sites spanning 1500 km in Inner Mongolian grasslands, compared the difference in aboveground, belowground biomass and below-aboveground biomass ratio (AGB, BGB, and B/A, respectively) among meadow steppe, typical steppe, and desert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 42 publications
3
17
0
1
Order By: Relevance
“…As a matter of fact, precipitation also had the strongest positive effect on AGB and BGB (Table 1). This phenomenon indicates that there is an integrated effect between temperature and precipitation on plant growth [37]. Our findings reinforce the idea that precipitation is major limiting factor that control the functions of ecosystems in terrestrial biomes, particularly in arid and semi-arid ecosystems [38][41].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As a matter of fact, precipitation also had the strongest positive effect on AGB and BGB (Table 1). This phenomenon indicates that there is an integrated effect between temperature and precipitation on plant growth [37]. Our findings reinforce the idea that precipitation is major limiting factor that control the functions of ecosystems in terrestrial biomes, particularly in arid and semi-arid ecosystems [38][41].…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we found that there was negative relationship of AGB with total nitrogen content. Thus, we concluded that the different responses of plants to nitrogen content are a result of different nitrogen deficiency levels of the local systems [37]. Soil phosphorous, generally regarded as the most critical factor for plant growth [48], the biomass was related with available phosphorous (Table 1, Figure 4).…”
Section: Discussionmentioning
confidence: 95%
“…Overall, the higher temperature, higher precipitation and lower elevation could result in the higher grassland biomass density in the southeast. Previous researches also suggested that carbon storage tended to accumulate in area where climatic factors were suitable (Gao et al, 2013a;Jiang et al, 2014;Kang et al, 2013;Mao et al, 2014;Wang et al, 2014;Xia et al, 2014). Moreover, anthropogenic factor (e.g., forage, fire, green project etc.)…”
Section: Spatial Distribution Of Grassland Biomass and Relative Uncermentioning
confidence: 99%
“…The region can be divided into three biomes: the arid desert biome in the west, the grassland biome in the center and the forest biome in the northeastern region [30] (Figure 1). The grassland is divided into three types: desert steppe, typical steppe and meadow steppe [31]. The MP is the main sandstorm source region for China.…”
Section: Study Areamentioning
confidence: 99%